Knowledge Explorers: Gamification in Higher Education - Pascoal, R. (Jornadas Ibéricas de Inovação Pedagógica, Universidade Europeia, 2025)
This paper presents a pedagogical innovation based on gamification tailored to higher education contexts. The proposed model, titled "Knowledge Explorers", integrates game elements such as scoring, missions, challenges, and rewards into academic curricula with the objective of enhancing student engagement, motivation, and skill development. Structured around immersive narratives and academic missions, students are positioned as explorers facing real-world challenges, promoting active learning, collaboration, and critical thinking. The gamified structure includes both individual and collaborative tasks, continuous formative feedback, and competitive ranking to stimulate performance and academic excellence. Expected outcomes include increased student motivation, improved academic performance, and the development of essential competencies such as leadership, research, and problem-solving. The model draws on established gamification frameworks and empirical evidence from the literature, contributing to the growing body of research on innovative instructional strategies in higher education.